To whom and when the upper gastrointestinal endoscopy is indicated in gastroesophageal reflux disease? What is the role of routine esophageal biopsy? Which endoscopic esophagitis classification should be used? - Kav, Taylan (Turkish Journal of Gastroenterology, 2017)
Abstract Gastroesophageal reflux disease (GERD) is a chronic disease characterized with heartburn and regurgitation symptoms. The prevalence of these symptoms in Turkey is reported to be as high as 20%. GERD negatively effects the quality of life along with the development of some complications due to chronic course. Upper gastrointestinal endoscopy is commonly performed for diagnosis and surveillance of complications in the context of GERD. However, there is no consensus in terms of timing and indications for endoscopy, use of esophagitis classification system, to obtain a biopsy sample or recommendation for surveillance endoscopy. In order to answer these questions, we performed a systematic literature search. In this article, we report our findings for these targeted questions and our proposals as a result of the national consensus program on GERD. Cite this article as: Kav T. To whom and when the upper gastrointestinal endoscopy is indicated in gastroesophageal reflux disease? What is the role of routine esophageal biopsy? Which endoscopic esophagitis classification should be used? Turk J Gastroenterol 2017;28(Suppl 1); S22-S25 Full Text Turkish